Sistem informasi inventaris barang STMIK Kreatindo Manokwari berbasis web - Lilis Indrayani; Zulkarnain (Universitas Muhammadiyah Riau, 2023)
Inventory is the process of procurement and inventory of goods owned by an office or company in carrying out operations, whether used in the future or a certain time period. An asset is an item that has economic value, economic value, use value, property value and special value that is owned individually or by a group that is focused on achieving organizational goals. Inventory is very important for the continuity of a company or agency, therefore a system is needed to manage office inventory data. STMIK Kreatindo Manokwari is one of the campuses in the city of Manokwari which has facilities and infrastructure that have not implemented technology-based inventory of goods, inputting data or assets is still done manually using Microsoft Excel, making asset data collection and archiving asset data less effective because it takes time old and unintegrated data collection which results in frequent duplicate data. Based on these problems, a website-based inventory information system was built using the waterfall method as a system development method which was carried out sequentially starting from analysis, design, coding, testing and supporting stages. The result of this research is a system that can make it easier to collect data on goods, check goods or move goods, which can be accessed anywhere and at any time if connected to the internet.